What causes the greater perceived similarity of consonant-transposed nonwords? - Schubert, Teresa (Q J Exp Psychol (Hove), 2017)
Nonwords created by transposing two non-adjacent orthographic consonants (CONDISER) have been reported to produce more priming for their baseword (CONSIDER), and to be classified as a nonword less readily than nonwords created by transposing two orthographic vowels (CINSODER). We investigate the origin of this difference and its relevance for theories of letter position coding. In the unprimed versions of the lexical decision and same–different tasks, a consonant–vowel difference was found in the transposition condition, not when those letters are substituted (Experiment 1). We found that when transpositions involved the disruption of a consonant cluster (OPMITAL), reaction times were slowed compared to when transpositions involved only letters that are separated (CHOLOCATE; Experiment 2). As transpositions more frequently disrupt in consonant clusters than vowel clusters, this introduces a confound in studies investigating consonant and vowel transposition effects. Consistent with the idea that letter order is harder to resolve in clusters, the difference between consonants and vowels was eliminated when transpositions involve singleton consonants or vowels rather than those in clusters (Experiment 3). These results suggest that the precision of position coding does not differ between consonants and vowels, but that consonant–vowel status plays a role in structuring orthographic representations.